The Effect of the Discovery Learning Model on Critical Thinking Skills and Science Learning Outcomes - Murniati Murniati; Syarifuddin Kune; Sukmawati Sukmawati (Electronic Journal of Education, Social Economics and Technology, 2025)
This research aims to examine the effect of the discovery learning model on critical thinking skills and science learning outcomes regarding the concept of environmental change in fifth-grade students at Gugus 1, Mangarabombang District, Takalar Regency. This study employs a quantitative research design using a Quasi-Experimental Design with a Posttest Only Control Group Design. The population consists of 132 fifth-grade students, and the sample of 44 students was selected using purposive sampling. Data collection techniques involved tests and observations. The data were analyzed using descriptive and inferential statistical methods. The results of the research indicate that the critical thinking skills and science learning outcomes are parametric data, which were tested using the Independent Samples Test, obtaining significance values of 0.000 0.05 and 0.039 0.05, respectively. Therefore, there is a partial effect of the discovery learning model on critical thinking skills and science learning outcomes in the environmental change concept for fifth-grade students at Gugus 1, Mangarabombang District, Takalar Regency. Additionally, the MANOVA test yielded a significance value of 0.000 0.05, rejecting H0 and accepting H1. This indicates that there is a simultaneous effect of the discovery learning model on critical thinking skills and science learning outcomes.